Teori dan Konsep Manajemen Biaya Pendidikan: Kajian Konseptual dan Praktis dalam Pembentukan Sumber Daya Manusia Bermutu - Suanti, Dwi Sari; Trilestari, Widya (LPPM UM Metro, 2026)
Scholarly discourse on educational finance has increasingly recognized that resource management decisions carry profound implications for institutional quality, yet most frameworks continue to treat cost management as a peripheral administrative concern rather than a core strategic function. This study departs from that tradition by positioning strategic cost management as an integrative governance mechanism through which educational institutions can purposefully align financial decisions with quality improvement goals. Drawing on a systematic review of peer-reviewed literature published between 2015 and 2024 and indexed in Scopus, DOAJ, and SINTA, this article pursues three objectives: mapping prevailing theoretical currents in educational cost management, pinpointing unresolved gaps in the scholarly conversation, and constructing a conceptual model that weaves together budgeting theory, cost-effectiveness analysis, human capital investment, governance principles, and performance-based accountability. The review surfaces a recurrent blind spot: researchers have largely examined these theoretical threads in isolation, leaving practitioners without a coherent, cross-context framework for decision-making. The five-dimensional model proposed here addresses this gap by treating each financial management function not as a standalone process but as an interdependent node in a continuous quality improvement cycle. Theoretical contributions include a synthesis of fragmented perspectives into a single actionable schema; practical contributions include concrete guidance for institutional leaders seeking to transform financial governance into a driver of sustainable educational quality.